Risk behaviors among villagers during a large outbreak of unidentified sudden death of poultry at a rural community in central of Thailand - Tiyanun, Ekasit; Pundee, Ritthirong; Udplong, Anusorn; Saengkul, Chutarat; Oprasertsawat, Mondhakarn (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 2 (2019): April-June 2019, 2019)
This cross-sectional study aimed to describe risk behaviors among villagers of Khaothong sub-district, a rural community in central of Thailand. 814 participants from 12 villages were interviewed with a survey form that was created to investigate a large outbreak of unidentified sudden death of poultry during August 2017. The interview was performed by trained public health students. The result showed that 33.86% of participants exposed to the infected poultry carcass during the outbreak. Among of them, 52.38% did not protect themselves while contact to the infected poultry carcass and 12.50% did not wash their hand after contact to the infected poultry carcass. Furthermore, nearly all of them had an improper practice about disposal of infected poultry carcass. These finding revealed that an enormous of villagers still had risk behaviors. Although this cross-sectional study had some limitations, the result could benefit public health officer and public health decision maker to conduct interventions and measures that will help to reduce risk behaviors among this population.      Keywords: risk, behavior, poultry, sudden death, outbreak